Cardiac protein kinases: the cardiomyocyte kinome and differential kinase expression in human failing hearts. (10th August 2015) - Fuller, Stephen J.; Osborne, Sally A.; Leonard, Sam J.; Hardyman, Michelle A.; Vaniotis, George; Allen, Bruce G.; Sugden, Peter H.; Clerk, Angela
Abstract: Aims: Protein kinases are potential therapeutic targets for heart failure, but most studies of cardiac protein kinases derive from other systems, an approach that fails to account for specific kinases expressed in the heart and the contractile cardiomyocytes. We aimed to define the cardiomyocyte kinome (i.e. the protein kinases expressed in cardiomyocytes) and identify kinases with altered expression in human failing hearts. Methods and results: Expression profiling (Affymetrix microarrays) detected >400 protein kinase mRNAs in rat neonatal ventricular myocytes (NVMs) and/or adult ventricular myocytes (AVMs), 32 and 93 of which were significantly up-regulated or down-regulated (greater than two-fold), respectively, in AVMs. Data for AGC family members were validated by qPCR. Proteomics analysis identified >180 cardiomyocyte protein kinases, with high relative expression of mitogen-activated protein kinase cascades and other known cardiomyocyte kinases (e.g. CAMKs, cAMP-dependent protein kinase). Other kinases are poorly investigated (e.g. Slk, Stk24, Oxsr1). Expression of Akt1/2/3, BRaf, ERK1/2, Map2k1, Map3k8, Map4k4, MST1/3, p38-MAPK, PKCδ, Pkn2, Ripk1/2, Tnni3k, and Zak was confirmed by immunoblotting. Relative to total protein, Map3k8 and Tnni3k were up-regulated in AVMs vs. NVMs. Microarray data for human hearts demonstrated variation in kinome expression that may influence responses to kinase inhibitor therapies. Furthermore, some kinases were up-regulated (e.g. NRK, JAK2, STK38L) or down-regulated (e.g. MAP2K1, IRAK1, STK40) in human failing hearts. Conclusion: This characterization of the spectrum of kinases expressed in cardiomyocytes and the heart (cardiomyocyte and cardiac kinomes) identified novel kinases, some of which are differentially expressed in failing human hearts and could serve as potential therapeutic targets.